Painting monkey or painting elephant? Some comments on measuring research in the creative arts - Elliott, Ronald (National Tertiary Education Union, 2011)
The ERA process has focused the notion of measurement on the creative arts and it is up to practicing creative academics to articulate the standards and defend the validity of way 'creatives' also create new knowledge. It is an opportunity to argue that the process of creative text creation is a form of research output in itself, not merely a text that is analysed conceptually, somehow before it exists.